Effect of different doses of hydrated C60 fullerene nanoparticles on ram semen during cool storage - Kaya, Seyma Ozer; Gungor, Ibrahim Halil; Cinkara, Serap Dayan; Acisu, Tutku Can; Koca, Recep Hakki; Akarsu, Serkan Ali; Turk, Gaffari (Tubitak Scientific & Technological Research Council Turkey, 2021)
The aim of this study was to determine the effect of different doses of hydrated C-60 fullerene (C(60)HyFn) nanoparticles on ram semen during cool storage at 5 degrees C. Semen samples were collected from 7 healthy Akkaraman rams by artificial vagina during nonbreeding season (April) 3 times for two weeks (3 replications), and samples having good initial sperm motility (> 70 %) and count (> 2 billion / mL) were pooled and diluted with tris-egg yolk based extender at 37 degrees C. Then, the diluted semen samples were divided into 15 aliquots control and 14 different C(60)HyFn groups (25 nM, 50 nM, 100 nM, 200 nM, 400 nM, 800 nM, 1 mu M, 5 mu M, 10 mu M, 20 mu M, 40 mu M, 60 mu M, 80 mu M, and 100 mu M), and stored at 5 degrees C up to 144th h. The motility (total, progressive, rapid, medium, slow, and static), kinematic (VCL, VSL, VAP, LIN, STR, WOB, ALH, and BCF), and some other spermatological parameters (dead, abnormal, damaged acrosome, and membrane intactness) were examined at 0, 12, 24, 48, 72, 96, 120, and 144th h. All C(60)HyFn doses except 25 nM, 50 nM, 60 mu M, 80 mu M, and 100 mu M had numerically higher total and progressive motility, membrane intactness and numerically lower static, dead and total abnormal spermatozoon ratios at the end of 144th h than control. The differences between 400 nM dose and control in membrane intactness, and also between 400, 800 nM doses and control in dead spermatozoon ratio were statistically significant (P < 0.0125). In conclusion, it is suggested that supplementation of any doses of C(60)HyFn between 100 nM and 40 mu M may be beneficial to keep some spermatological parameters at high level during the short-term storage of ram semen at 5 degrees C.
Keywords: Hydrated C-60 fullerene; cool storage; spermatozoon; ram